EVALUATION OF THE MEDICAL CARE ARRANGEMENT FOR NEWBORNS IN CONDITIONS OF A PATIENT-ORIENTED APPROACH - O, Ivanov D.; K, Yuryev V.; E, Moiseeva K.; A.V, lekseeva; Sh.D., Kharbediya (International Journal of Psychosocial Rehabilitation, 2020)
--Today, in the search for new approaches to improving the quality of medical services, the patients’opinion can serve as one of the criteria for a comprehensive evaluation of the activities of a medical organization. In order to evaluate the satisfaction of mothers with providing medical care to newborns by random sampling, an anonymous survey was conducted of 1026 mothers whose children were born in the perinatal center in 2018-2019. It was found that 71.9% of mothers were hospitalized to the perinatal center as planned, on the doctor’s referral due to the state of their health or the health of the child.79.4% of respondents were served under compulsory medical insurance. On average, mothers rated the work of doctors who provide medical care to newborns by 4.6±0.11 points, and average medical personnel - by 4.4±0.09 points. However, 13.7% of mothers indicated that doctors were not always tactful and polite and 41.2% of women – medical nurses. 15.9% of mothers were partially dissatisfied with the conditions of the child’s stay in the perinatal center.In most cases, the reasons for dissatisfaction were unregulated temperature conditions in the room (47.4%), inattentiveness of medical staff (9.1%) and lighting (14.8%). In general, the medical care arrangement for newborns in the perinatal center received a fairly high rating from mothers (an average of 4.4±0.09 points) and 93.8% of respondents would recommend this maternity facility for providing medical care to children.